Valuation and Business Performance Analysis of PT Barito Renewables Energy Tbk. (BREN) Post-IPO - Alviandi Taniwidjaja, Davin; Murtaqi, Isrochmani (DINASTI RESEARCH, 2025)
This study analyzes the valuation and financial performance of PT Barito Renewable Energy Tbk (BREN), specifically examining its post-IPO performance within Indonesia's renewable energy sector. Employing the Discounted Cash Flow (DCF) method alongside a Free Cash Flow to the Firm (FCFF) approach and Relative Valuation metrics (including Price Earnings Ratio, Price to Book Value, and EV/EBITDA), the findings indicate a significant overvaluation of BREN's stock, with an intrinsic value per share derived from the DCF method estimated at 0.00832, which starkly contrasts with its market price of 0.486. This discrepancy points to a substantial market overvaluation, influenced by speculative trading and heightened investor enthusiasm. Furthermore, BREN's financial profile reveals elevated leverage ratios, such as Debt-to-Equity and Debt-to-EBITDA, in comparison to industry peers, underscoring inherent financial risks despite commendable operational efficiency evidenced by an 84% EBITDA margin. The study emphasizes the necessity of reconciling market expectations with financial fundamentals, providing critical insights into the dynamics of overvaluation among emerging renewable energy firms, and proposing strategies to enhance financial sustainability while supporting Indonesia’s transition toward renewable energy.